Termites Attack on Residential Houses at Sialangmuggu, Tuah Madani, Pekanbaru - Andi Saputra; Vebrita Sari; Febri Ayu; Syamsul Bachry; Awari Susanti (Journal of Engineering Science and Technology Management, 2022)
Termites can damage wood in building construction and other cellulosic materials in buildings, making them a pest that causes problems for humans. This research is expected to provide information on how insect pest termites (Coptotermes curvignathus) are disturbed in Villa Savana Housing, Sialang Munggu, Tuah Madani, Pekanbaru. Termites that are found in the presence of their burrows are then collected. The method used is the hand-picked method where this method directly uses the hand when the presence of termites is known. Surveys and interviews were conducted to determine the intensity of damage to houses. Based on the results of the study, it can be concluded that in Villa Savana Housing there is one type of subterranean termite, namely C. curvignathus. Then the results of the survey of damage to house buildings show that most of the house buildings are in good condition (80.03%). In addition, damage due to dry-wood termite attacks was also found, but no examples of termites were found.